Development of white organic light emitting diodes based on carbazole-derived compounds - Melnykov, Serhii; Bilas, Orest (Technology audit and production reserves, 2024)
The object of research is the thermal, photophysical, and electrophysical properties of newly synthesized carbazole-derived compounds and organic light-emitting structures based on them. The problem consists in the comprehensive solution of scientific and technical problems of improving the characteristics of white organic light-emitting diodes (OLED), expanding their emission spectrum, improving color and energy characteristics. The results of the thermal, electrophysical and photophysical properties of the investigated carbazole compounds were obtained. They demonstrated good thermal stability. Absorption spectra in solid films were recorded in the range of 300–350 nm. Photoluminescence spectra were observed at a wavelength of 407 nm for the first and second compounds and 430 nm for the third. The quantum yield of photoluminescence in films for compounds 1, 2, and 3 was 16 %, 7 %, and 7 %, respectively. Organic light-emitting structures of white emission color with color coordinates (0.31, 0.35), (0.32, 0.34) and (0.38, 0.34) close to natural white light (0.33, 0.33) were formed using the thermovacuum sputtering method. The turn-on voltage of the white OLED is 6 V, the maximum brightness of the light-emitting structures was 10,000 cd/m2. The devices demonstrated a sufficiently high external quantum efficiency of 5 % to 7 %. The obtained results are explained by the mixing of different types of electroluminescence, namely excitonic and electromeric. Electromeric radiation is obtained due to transport layers. This approach improves such an important parameter of white light as its quality, which includes color coordinates and color rendering index. Due to their color characteristics, white light-emitting diodes based on carbazole-derived compounds are promising candidates for use in modern lighting systems. A separate advantage of these light-emitting structures is the dependence of the color gamut of their radiation on the applied voltage. In addition, organic LEDs based on carbazole-derived compounds have low energy consumption and are environmentally friendly due to the absence of toxic substances in their design, which creates prerequisites for both global energy savings and a reduction of the industrial burden on the environment.